2008
DOI: 10.1113/jphysiol.2007.149294
|View full text |Cite
|
Sign up to set email alerts
|

‘Pressure–flow‘‐triggered intracellular Ca2+ transients in rat cardiac myocytes: possible mechanisms and role of mitochondria

Abstract: Cardiac myocytes, in the intact heart, are exposed to shear/fluid forces during each cardiac cycle. Here we describe a novel Ca 2+ signalling pathway, generated by 'pressurized flows' (PFs) of solutions, resulting in the activation of slowly developing (∼300 ms) Ca 2+ transients lasting ∼1700 ms at room temperature. Though subsequent PFs (applied some 10-30 s later) produced much smaller or undetectable responses, such transients could be reactivated following caffeineor KCl-induced Ca 2+ releases, suggesting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
53
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 49 publications
(67 reference statements)
4
53
0
Order By: Relevance
“…In summary, the literature is replete with studies suggesting that a mitochondrial NCX block by CGP results in intracellular Ca 2ϩ store depletion in various cell systems (Griffiths et al, 1997;Malli et al, 2005;Belmonte and Morad, 2008). In this study, the nature of CGP interactions with SR transporters was explored, and we found that there is direct CGP action on SERCA and RyRs.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In summary, the literature is replete with studies suggesting that a mitochondrial NCX block by CGP results in intracellular Ca 2ϩ store depletion in various cell systems (Griffiths et al, 1997;Malli et al, 2005;Belmonte and Morad, 2008). In this study, the nature of CGP interactions with SR transporters was explored, and we found that there is direct CGP action on SERCA and RyRs.…”
Section: Discussionmentioning
confidence: 92%
“…Among mitochondrial transporters, the 7-chloro-5-(2-chlorophenyl)-1,5-dihydro-4,1-benzothiazepin-2(3H)-one [CGP-37157 (CGP)]-sensitive Na ϩ / Ca 2ϩ exchanger (NCX) may mediate SR Ca 2ϩ load and release (Szalai et al, 2000;Malli et al, 2005;Csordá s and Hajnóczky, 2009). Indeed, CGP has been found to significantly affect intracellular Ca 2ϩ signaling in smooth, cardiac, and skeletal muscle cells and in nonmuscle systems (Griffiths et al, 1997;Malli et al, 2005;Belmonte and Morad, 2008;Liu and O'Rourke, 2008;Chalmers and McCarron, 2009;Csordá s and Hajnóczky, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Belmonte and Morad used pressurized flows (PFs) of solutions to imitate the hemodynamic stress to cardiomyocyte. 10 However, their PFs produced a pressure head of 20.5 mm Hg, which was significantly lower than the blood pressure in human hypertension (higher than 140 mm Hg). Recently, Giridharan et al developed a microfluidic cardiac cell culture model (lCCCM) that incorporated pulsatile stretch and pressure on cardiac cells in a single device.…”
Section: Introductionmentioning
confidence: 87%
“…Shear stress of comparable strength induces a distinct spontaneous Ca 2+ transient (timeto-peak, T p : 130 ms) in fura-2-AM-loaded rat atrial myocytes, as shown by epifluorescence measurement [10]. This shear-induced global Ca 2+ signal occurs faster than longitudinal Ca 2+ waves in terms of Ca 2+ release (T p ≥300 ms).…”
Section: Introductionmentioning
confidence: 95%
“…A series of recent reports have suggested that cardiac myocytes significantly alter their membrane conductance and Ca 2+ signaling in response to shear stress [9][10][11][12][13][14]. It has been reported that shear stress in atrial myocytes enhances Ca 2+ spark occurrence and induces longitudinal Ca 2+ waves under resting conditions [9,12].…”
Section: Introductionmentioning
confidence: 99%